THE BIOSYSTEMATIC IMPERATIVE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
With the wider awakening of the world's environmental conscience, and the global commitment to the sustainable use of biodiversity, has come the need to know much more precisely and comprehensively than before the specific composition of biological...